INVESTMENT PROJECT ANALYSIS THE CASE OF BINUNGAN BLOCK 10 MINE PROJECT - Irwan, Maurys
The Binungan Block 10 Mining Project is marginal from the previous economic valuation. Higher operational costs, land issues and low coal quality have become management's considerations for delaying operations. However, the demand for coal has increased significantly recently, which has driven coal prices to historical highs. The management of PT Berau Coal considered accelerating the commencement of mining and asked the mine planner to carry out an Investment Project Analysis for the Binungan B 10 Mining Project.